2014
DOI: 10.1093/icvts/ivu381
|View full text |Cite
|
Sign up to set email alerts
|

Role of sevoflurane in organ protection during cardiac surgery in children: a randomized controlled trial

Abstract: Sevoflurane did not provide superior myocardial protection in our general paediatric cardiac surgical population. In children under 6 months, however, sevoflurane might be beneficial in comparison with midazolam. The conditioning effects of sevoflurane in specific paediatric subgroups need to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
9
0
4
Order By: Relevance
“…Studies have reported that the cardioprotection mechanism of inhaled anesthetics such as, volatile anesthetics open intracellular K ATP channels, activate adenosine receptors, and inhibit Na + /K + pump [1, 8, 28, 29]. Studies have also reported that the cardioprotection mechanism of propofol is related to its anti-inflammatory, immunomodulatory and antioxidant properties [21, 30, 31]. Nevertheless, many studies, such as some prospective randomized controlled trials [1013, 32] and observational study [14] in adult patients indicated some contradicting results on the cardioprotection between volatile and non volatile agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that the cardioprotection mechanism of inhaled anesthetics such as, volatile anesthetics open intracellular K ATP channels, activate adenosine receptors, and inhibit Na + /K + pump [1, 8, 28, 29]. Studies have also reported that the cardioprotection mechanism of propofol is related to its anti-inflammatory, immunomodulatory and antioxidant properties [21, 30, 31]. Nevertheless, many studies, such as some prospective randomized controlled trials [1013, 32] and observational study [14] in adult patients indicated some contradicting results on the cardioprotection between volatile and non volatile agents.…”
Section: Discussionmentioning
confidence: 99%
“…A sample size of 70 cases would have a power of 95% to detect a difference in the level of cTnI of 2 ng ml −1 as a primary end-point using a two-sample t -test with 0.05 two-sided significance level [11, 20, 21]. Patient characteristics were compared with an unpaired t test and Fisher exact test where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical studies and meta-analyses have demonstrated the contribution of a potential cardioprotective strategy by sevoflurane postconditioning. 17,22,23,40 Related fundamental research assumed the involvement of the protein kinase C, PI3K/Akt, and extracellular signal-related kinase 1/2 pathways. 23 The safety and efficacy of DEX in perioperative cardiac surgery have been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Он обладает гипнотическим, анальгетическим и миорелаксирующим эффекта- Ингаляционные анестетики обладают кардиопротективными свойствами. Большинство исследований в этой области посвящено изучению защитных свойств галогенсодержащих анестетиков, в частности изофлурана и севофлюрана [12][13][14]. Применение севофлюрана и изофлурана при вы-полнении операций реваскуляризации миокарда как в условиях искусственного кровообращения, так и на работающем сердце, вызывает эффект фармакологического прекондиционирования и уменьшает степень ишемического повреждения миокарда.…”
Section: результаты исследования и их обсуждениеunclassified